Analysis Satisfaction Public To Service In Kua Revitalization Of Panca Rijang District - Muammar Hijaz; Jamaluddin Ahmad; Andy Nilvana (JHSS (JOURNAL OF HUMANITIES AND SOCIAL STUDIES), 2023)
Minister of Religion issues Minister of Religion Decree Number 758 of 2001 concerning the Revitalization of Subdistrict Religious Affairs Offices. The research aims to find out the level of public satisfaction measured through 9 dimensions (ICM) to service in the Religious Affairs Office of the District of Panca Rijang which has been revitalized. Furthermore, the 9 Dimensions of Public Satisfaction will be correlated with the General Satisfying Perception to find out what satisfaction factors most affect overall satisfaction. This research uses quantitative methodology while the type of research is descriptive research. Data collection techniques use interviews, observations, documentation, and questionnaires. Primary data sources are obtained from sample, determination of sample using purposive sampling techniques while secondary data is derived from related instance documents. Process and analyze data using descriptive methods.The results of the research showed that, based on the results of our research, it was found that the quality of service at Religious Affair Office of Panca Rijang was very good (79.18%) after revitalization. In general, public satisfaction perception of Religious Affair Office’s service (76.61%). It was noted that the nine dimensions of service can predict satisfaction of service in general with a regression of 74%. There are six services dimensions that are positively correlated with the general satisfaction; simplicity of procedures, officer discipline, speed of service, decency and hospitality of officers, justice of officials, and a sense of comfort as well